Evaluation on direct interspecies electron transfer in anaerobic sludge digestion of microbial electrolysis cell - Zhao, Zisheng; Zhang, Yaobin; Quan, Xie; Zhao, Huimin (Bioresource technology, 2016)
•Carbon-felt addition increased the methane production in anaerobic sludge digestion.•Hydrolysis and acidification process was enhanced in the MEC reactor.•A voltage on electrode further improved the performance of the anaerobic digestion.•DIET between VFA-oxidizing bacteria and methanogens was promoted in MEC reactor. Increase of methanogenesis in methane-producing microbial electrolysis cells (MECs) is frequently believed as a result of cathodic reduction of CO2. Recent studies indicated that this electromethanogenesis only accounted for a little part of methane production during anaerobic sludge digestion. Instead, direct interspecies electron transfer (DIET) possibly plays an important role in methane production. In this study, anaerobic digestion of sludge were investigated in a single-chamber MEC reactor, a carbon-felt supplemented reactor and a common anaerobic reactor to evaluate the effects of DIET on the sludge digestion. The results showed that adding carbon felt into the reactor increased 12.9% of methane production and 17.2% of sludge reduction. Imposing a voltage on the carbon felt further improved the digestion. Current calculation showed that the cathodic reduction only contributed to 27.5% of increased methane production. Microbial analysis indicated that DIET played an important role in the anaerobic sludge digestion in the MEC.